To show that the arithmetic sequence formula \( a_n = 6 + (n - 1) \cdot 8 \) has the same structure as a linear function, we can rearrange the formula into the form \( a_n = mx + b \), where \( m \) is the slope and \( b \) is the y-intercept.
Starting from the given formula:
\[ a_n = 6 + (n - 1) \cdot 8 \]
We can distribute the 8:
\[ a_n = 6 + 8n - 8 \]
Now, simplify it:
\[ a_n = 8n - 2 \]
This shows that the arithmetic sequence can be expressed in the form of a linear function where \( m = 8 \) (the coefficient of \( n \), or the slope) and \( b = -2 \) (the constant term).
Now, we need to find the linear function equation that matches this structure, specifically:
\[ y = 8x - 2 \]
So the correct response is:
y = 8x - 2